2019
DOI: 10.1007/s12665-019-8565-9
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater recharge assessment in dry years

Abstract: The climate change that has been observed in recent years has affected the water balance, including the groundwater resources recharge. The paper is an attempt to evaluate the groundwater recharge in dry years. The initial stage of the research consisted of selecting the years when meteorological and hydrological droughts occurred, with use of the standardized indices Standardized Precipitation Index (SPI) and Standardized Water Level Index (SWI). With the use of the WetSpass model for selected periods and for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Poland is situated in the area of Europe that is endangered by forest fires, which are primarily connected with its geographic location between the contrasting oceanic and continental climates (Kundzewicz and Matczak 2012). It is also characterized by permanent factors influencing the water balance, such as precipitation and cyclical long-term droughts, leading to reductions in groundwater (Kubicz et al 2019). The fully biocenotic conditions of the forests and their uniform age and species structure make them particularly vulnerable to fires (Ubysz et al 2006;Szczygieł 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Poland is situated in the area of Europe that is endangered by forest fires, which are primarily connected with its geographic location between the contrasting oceanic and continental climates (Kundzewicz and Matczak 2012). It is also characterized by permanent factors influencing the water balance, such as precipitation and cyclical long-term droughts, leading to reductions in groundwater (Kubicz et al 2019). The fully biocenotic conditions of the forests and their uniform age and species structure make them particularly vulnerable to fires (Ubysz et al 2006;Szczygieł 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Rainfall is the main source for groundwater natural recharge, which is regulated by an array of physical and climatic factors, such as geological framework, soil type, slope, vegetation, land cover, and evapotranspiration [9][10][11]. According to Scanlon et al [12] and Singh et al [13], there is no universal approach to study groundwater recharge and that is why the amount of methods reported in scientific literature is high.…”
Section: Introductionmentioning
confidence: 99%